2018
DOI: 10.1096/fj.201700941rr
|View full text |Cite
|
Sign up to set email alerts
|

CD5L is upregulated in hepatocellular carcinoma and promotes liver cancer cell proliferation and antiapoptotic responses by binding to HSPA5 (GRP78)

Abstract: CD5-like (CD5L) is a soluble scavenger cysteine-rich protein that modulates inflammatory responses. We studied the involvement of CD5L in liver cancer. Immunohistochemistry (IHC) of CD5L in 60 hepatocellular carcinomas and 34 adjacent nontumor livers, showed that CD5L staining was higher in tumor than in nontumor tissue (Mann-Whitney test; P = 0.0039). High CD5L correlated with elevated proliferation (Ki67, linear regression; P < 0.0001) and lower patient event-free survival (log-rank; P = 0.0185). Accordingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 53 publications
1
45
2
Order By: Relevance
“…A recent study has demonstrated that increasing the level of autophagy decreases hepatic I/R injury (36). Previous studies have reported that CD5L increases macrophage survival and liver cancer cell survival by enhancing autophagy (12,16). These data indicate the participation of CD5L in promoting autophagy.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…A recent study has demonstrated that increasing the level of autophagy decreases hepatic I/R injury (36). Previous studies have reported that CD5L increases macrophage survival and liver cancer cell survival by enhancing autophagy (12,16). These data indicate the participation of CD5L in promoting autophagy.…”
Section: Discussionmentioning
confidence: 83%
“…Various disease models, including cancer, have demonstrated that CD5L participates in cellular functions by preventing apoptosis (33,34). Human CD5L has also been demonstrated to inhibit apoptosis in liver cancer cell lines in response to cisplatin by inducing autophagy (12). A previous study has suggested that CD5L serves cytoprotective effects by binding to the CD36 receptor (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LYVE1, CST3, and NCAM1 are also reportedly involved in placental vascular remodeling (Pawlak et al, 2019;Song et al, 2010;Zhang, Xu & Han, 2019). GRN, CD5L, ENO1, CHL1, CRISP3, VASN, and TNIK promote the invasive ability of tumor cells (Aran et al, 2018;Bhandari et al, 2019;Buhusi et al, 2003;Chon et al, 2016;Song et al, 2014;Voshtani et al, 2019;Wang et al, 2019). By contrast, SEMA4B, KRT1, KRT9, FBLN1, and PTGDS are involved in the anti-invasive activity of tumor cells (Blanckaert et al, 2015;Jian et al, 2015;Marano et al, 2018;Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%